2021
DOI: 10.1007/s13668-021-00355-3
|View full text |Cite
|
Sign up to set email alerts
|

To Detect and Reject, Parallel Roles for Taste and Immunity

Abstract: Purpose of Review From single cells to entire organisms, biological entities are in constant communication with their surroundings, deciding what to ‘allow’ in, and what to reject. In very different ways, the immune and taste systems both fulfill this function, with growing evidence suggesting a relationship between the two, through shared signaling pathways, receptors, and feedback loops. The purpose of this review was to explore recent reports on taste and immunity in model animals and in humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Several studies have shown that obesity is associated with taste changes, particularly a reduction in taste acuity and taste bud abundance. For example, hypothalamic and brainstem T1R3 and T2R116 taste receptors as well as signaling molecules such as Gα14 and TRPM5 were downregulated by obesity in mice [ 137 , 138 ]. In humans, loss of taste was associated with selection of high caloric foods [ 139 ]; however, the evidence linking taste responses and taste gene polymorphism is limited [ 140 ] Conversely, weight loss such in patients undergoing bariatric surgery results in rapid changes in taste which may be due to the overall reduction in inflammation and/or in response to physiological and metabolic changes due to the anatomical reconfiguration of the GI tract [ 141 , 142 ].…”
Section: Clinical Implication Of Microbiota/taste Interactionsmentioning
confidence: 99%
“…Several studies have shown that obesity is associated with taste changes, particularly a reduction in taste acuity and taste bud abundance. For example, hypothalamic and brainstem T1R3 and T2R116 taste receptors as well as signaling molecules such as Gα14 and TRPM5 were downregulated by obesity in mice [ 137 , 138 ]. In humans, loss of taste was associated with selection of high caloric foods [ 139 ]; however, the evidence linking taste responses and taste gene polymorphism is limited [ 140 ] Conversely, weight loss such in patients undergoing bariatric surgery results in rapid changes in taste which may be due to the overall reduction in inflammation and/or in response to physiological and metabolic changes due to the anatomical reconfiguration of the GI tract [ 141 , 142 ].…”
Section: Clinical Implication Of Microbiota/taste Interactionsmentioning
confidence: 99%
“…Therefore, it is not unexpected that several mechanisms of human innate immunity are based on components of taste signal transduction [7]. In this line, several studies in the literature have reported that these two systems can interact and influence each other [37]; in fact, taste alterations have been linked with several inflammatory and autoimmune disorders (e.g., systemic lupus erythematosus and Sjögren's syndrome) [38] and upper respiratory infections, with COVID-19 as a representative case.…”
Section: Discussionmentioning
confidence: 99%
“…Food antigens and the immune system have the oral cavity as the first meeting place. Here, the functional roles of immunity and taste overlap, deciding what to ‘allow’ in and what to reject 34 . Thus, it is foreseeable that these systems may interact and influence each other.…”
Section: Discussionmentioning
confidence: 99%